Meninjau Manajemen Risiko dan Tingkat Kesehatan Bank Syariah - Nastiti, Hasna Mumtaz; Cupian, Cupian (ITB AAS INDONESIA Surakarta, 2024)
Risk management is the key to ensuring the stability and soundness of Islamic Banks. As an intermediary institution that serves various products and services, it certainly faces various uncertainties. Risk management practices help Islamic banks identify problems early, evaluate and manage risks, mitigate negative impacts on the performance and business continuity of Islamic Banks, and increase or improve the Bank Soundness Level. Bank soundness indicates a bank's ability to carry out banking operations and fulfill all its obligations. The research objects in this study are BCA Syariah and Bank Mega Syariah. This research uses a quantitative approach to identify whether or not there are differences in risk profiles and soundness levels, and qualitative with literature studies to see risk management strategies between the two Islamic Banks. The Mann-Whitney test shows that the risk profile of BCA Syariah and Bank Mega Syariah is classified as a low category. Then, the health level of the two Islamic banks is ranked second, which is healthy.